Assessment of disease activity in rheumatoid arthritis: recommendations and practice - Yu.A. Olyunin (Современная ревматология, 2014)
The results of studies conducted over the past two decades were used to elaborate EULAR recommendations for the management of rheumatoid arthritis (RA); the updated recommendations have recently been published. In accordance with these recommendations, the tactics in management of each patient is determined by the disease activity. This indicator determines the frequency of examination for the patient, selection of an anti-rheumatic drug, and the need for therapy correction. Methotrexate is recommended to patients with active RA (high or moderate activity) naÏve to disease-modifying anti-rheumatic drugs (DMARDs). Another DMARD can be used for patients with lower activity of RA. Therapy effectiveness is evaluated as soon as 3 months after its prescription. Clinical improvement (decrease in RA activity from high to moderate) needs to be achieved by this time. However, the aim of therapy is to achieve low disease activity or remission (that needs to be achieved earlier than 6 month after the therapy was started) rather than clinical improvement only. If the maximum dose of a drug results neither in clinical improvement after 3 months nor in low activity after 6 months, the therapy should be corrected. EULAR experts recommend using the overall score that includes joint score indices (DAS28, SDAI or CDAI) to assess the level of RA activity.